Factors limiting karoo shrub populations in the Nama-Karoo - Hebbelmann, Lisa (University of the Witwatersrand, Johannesburg, 2023)
The Nama-Karoo Biome occupies the central and western region of South Africa. Nama-Karoo shrublands are dominated by karoo dwarf shrubs and in the wetter eastern regions annual and perennial grasses are interspersed among shrubs. Rainfall and grazing are the main drivers of vegetation change in the Nama-Karoo. Stocking rate, season of grazing and animal type are important influences on vegetation community composition, and rainfall determines shrub growth and the abundance of grass. More recently, fire has been identified as a driver of vegetation change. Understanding vegetation change is important for land managers in the Nama-Karoo as changes in karoo shrub communities have implications for forage availability. This thesis is focused on understanding how grazing, fire, grass-shrub competition, and soil moisture and temperature affect the composition, structure, growth and phenology of karoo shrubs in the Eastern Upper Karoo. Livestock type and stocking rate vary greatly over the greater Nama-Karoo area. Plant composition data from the Afrikaner-Hereford grazing trial at Grootfontein show that grazing has a strong legacy effect on Karoo rangelands and grazing-induced compositional and structural changes are clear many years after grazing has ceased. Different sheep breeds affect karoo shrub communities in different ways. There was a severe negative effect of heavy stocking with dorper sheep on karoo shrub communities and their structure; the impacts of merino sheep were significant but less severe. Effects of animal type and stocking rate were not consistent across the sites but appear to be dependent on edaphic factors. Soil physical properties appear to play an important part in determining the long term effects of grazing on karoo shrub communities. Fire is a novel disturbance in the Karoo. Nine sites which had experienced fire for the first time in history were studied for the effect of fire on the composition and structure of their shrub communities. The immediate effect of fire on karoo shrub communities was severe and the legacy effect of fire was significant. The nature of recovery after a fire depended on the abundance of fire-intolerant obligate reseeder shrubs that are killed by fire compared to the abundance of fire-tolerant resprouting shrubs. Rainfall and grazing management were important determinants of shrub recovery after a fire. As rainfall increases, grass biomass is predicted to increase, and this may result in fire becoming a more frequent occurrence in the Nama-Karoo. During periods of high rainfall, the biomass of grass in the Nama-Karoo increased at the expense of shrub cover. The effect of grass-shrub competition on shrub growth and phenology is not adequately explained by existing hypotheses of niche separation and succession. A field experiment which examined the growth and phenology of karoo shrubs in the presence of grass (unclipped control) and the absence of grass (grass removed by clipping) did not provide evidence of a competitive effect from grass on shrub growth or phenology. It did, however, provide valuable insight into how shrub growth and phenology are influenced by soil moisture and temperature. Rainfall in the Nama-Karoo is sporadic and a karoo shrub’s ability to utilise soil moisture will determine its ability to grow and successfully recruit. Shrub growth, with or without grasses in the vicinity, was strongly correlated with rainfall, but this was modified by temperature. Similarly, soil moisture and temperature were important for stem growth and phenology. Flowering occurred in response to soil moisture all year round but seeding occurred mainly during summer. Patterns of growth and phenology can be used by land managers to optimise shrub production while allowing phenological processes to take place. The findings of this study provide further insight into how grazing, fire, competition, soil moisture and temperature influence shrub populations and their structure, and these are discussed in the context of an existing state-and-transition model for the Eastern Upper Karoo. The importance of animal type and stocking rate, and how they vary across Nama-Karoo landscapes, is highlighted. The legacy of both grazing and fire reveal that the transitions between the alternate states of Nama-Karoo shrublands are not easily reversed in a management timeframe. It may take decades for a community changed by grazing or fire, acting independently or in conjunction, to return to their former state even under benign management. These findings along with a description of how soil moisture and temperature influence shrub growth and phenology have been used to make ecologically sound recommendations for the management of Nama-Karoo rangelands. Future research is needed to improve our understanding of how edaphic factors limit and influence karoo shrub populations across a variety of karoo landscapes, how repeat fires might change karoo vegetation, and whether temperature and the presence of pollinators influences shrub seed set. An assessment of the economic implications of vegetation change in the Nama-karoo is warranted so that management recommendations can be made with both ecology and economy in mind.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Nama-Karoo; Fire ecology; Competition; Grazing; State change; Climate change; Rangeland management; UCTD; SDG-15: Life on land